Analisis Strategi Pemasaran dalam Meningkatkan Daya Tarik dan Loyalitas Pengunjung: Studi Kasus Enauto Café di Nabire - Hellena Griffith Lasamahu; Ajumat Fimbay; Lamba Toding Palimbu (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to analyze the marketing strategies implemented by Enauto Café to enhance customer attraction and loyalty in Nabire. A descriptive qualitative method was employed through direct observation, interviews with the café manager and customers, and questionnaires distributed to 40 respondents. The findings indicate that social media-based marketing strategies, strong visual branding, and consistent customer service contribute significantly to customer loyalty. However, there are notable weaknesses in direct promotion and menu variety. Therefore, strengthening local promotion efforts and product innovation are recommended as strategic improvements.